An Assessment of the Magmatic Conditions of Late Neoproterozoic Collisional and Post-collisional Granites From the Guéra Massif, South-Central Chad - Pham, Chi Thi; Shellnutt, J. Gregory; Yeh, Meng-Wan; Iizuka, Yoshiyuki (Frontiers in Earth Science, 2020)
The Guéra Massif, in South-Central Chad hosts granitic rocks that were emplaced during distinct intervals (595-590 Ma; ~570 Ma; ~560 Ma) of the Late Ediacaran Central African Orogenic Belt. To the northwest of the Guéra Massif, younger post-collisional granites (554-545 Ma) are found near Lake Fitri. The older ( 590 Ma) rocks have geochemical characteristics of collisional granites whereas the younger ( 570 Ma) rocks are similar to post-collisional granites. Biotite and amphibole were analyzed to constrain the magmatic conditions of the granites. The biotite from the collisional granites tends to have higher Al and Ti and lower Fe# (Fe#average  0.67) than the post-collisional granites (Fe#average  0.88). The average crystallization temperatures range from 696 ± 37oC to 612 ± 8oC, with the average pressure of crystallization from 0.25 ± 0.09 GPa to 0.13 ± 0.02 GPa, and redox conditions between the nickel-nickel oxide (NNO) and quartz-fayalite-magnetite (QFM) buffers. The biotite crystallization temperatures of the post-collisional rocks are generally lower than the collisional rocks (570 Ma = 630 ± 26oC to 619 ± 30oC, 560 Ma = 626 ± 20oC to 607 ± 4oC, 550 Ma = 639 ± 18oC to 612 ± 13oC), but the crystallization pressures are similar (0.27 ± 0.05 GPa to 0.14 ± 0.04 GPa). The redox conditions transition from the QFM buffer to the wüstite-magnetite (WM) buffer. In contrast, the biotite from the Lake Fitri post-collisional granites crystallized at higher pressure (0.39 ± 0.08 GPa to 0.35 ± 0.03 GPa) but similar redox conditions. The amphiboles in the younger (~590 Ma) collisional granites and the post-collisional granites yielded crystallization pressure estimates that are generally higher (~0.6 GPa to ~0.1 GPa) than the biotite estimates but there is overlap. The difference in pressure may be due to the timing of crystallization and/or crystal redistribution. Overall, there appears to be a secular change from high to low temperature and pressure whereas the redox conditions appear to be spatially related. The biotite crystallization pressure of the Lake Fitri granites suggests they were likely emplaced into a different domain/terrane of the Saharan Metacraton than the Guéra Massif.